Antisipasi Ekohidrodinamika Pengendalian Eutrofikasi Mendukung Sistem Irigasi Jatiluhur yang Berkelanjutan - Eko Winar Irianto (Jurnal Irigasi, 2015)
Eutrophication is one of the serious problems in a reservoir which may disturb the water supply system in the downstream. Jatiluhur Dam is the reservoir with eutrophication problems. One of the methods to control water quality in Jatiluhur Reservoir is ecohydrodynamic method by utilizing Hollow Jet Valve (HJV). A comprehensive HJV operations is required to maintain the already-planned reservoir operation. This paper informs how to analyzes the effect of HJV operation to water quantity and water quality in the downstream of Jatiluhur Reservoir. Analysis result shows that the water level decreases in Jatiluhur Reservoir and increases in Curug Barage while HJV gate operation is still in line with water supply plan and reservoir operation, especially for irrigation sector. Furthermore, the result also shows that HJV operation increases BOD, Total N, and Total P pollutants and still complies with Class-3 of Indonesian National Standard of Water Quality for irrigation water. DO is the most sensitive parameters and 67% increase of BOD might develop an anaerob condition in the hypolimnion layer after the reservoir restoration. Therefore, sinergyc programs between reservoir restoration and water conservation in irrigation network are still required.